2005
DOI: 10.1002/cne.20653
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear STAT3 translocation in guinea pig and rat brain endothelium during systemic challenge with lipopolysaccharide and interleukin‐6

Abstract: During systemic inflammation, cytokines are released by immune-competent cells into the circulation, which in turn signal the brain to mediate brain-controlled signs of illness. Cytokine-responsive brain cells can be mapped by histological analysis of cytokine-induced transcription factors or transcription factor-associated molecules revealing different cell phenotypes that respond to activation of the immune system. Critical sites mediating cytokine-dependent immuneffector functions can be divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
65
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
14
65
2
Order By: Relevance
“…This was confirmed by our recent study showing that nuclear STAT3 translocation following LPS treatment in guinea pigs occurs only after plasma concentrations of IL-6 reach a critical level (50), also suggesting that LPS-induced STAT3 activation is IL-6 dependent. We have now confirmed these observations and those of others (19,22,24,51) by demonstrating unequivocally that this is indeed the case. Most importantly, the present study showed that STAT3 activation using the paradigms described occurred in endothelial cells lining the vasculature of the brain, adding support to previous observations that these cells constitute important targets for circulating pyrogens (36).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was confirmed by our recent study showing that nuclear STAT3 translocation following LPS treatment in guinea pigs occurs only after plasma concentrations of IL-6 reach a critical level (50), also suggesting that LPS-induced STAT3 activation is IL-6 dependent. We have now confirmed these observations and those of others (19,22,24,51) by demonstrating unequivocally that this is indeed the case. Most importantly, the present study showed that STAT3 activation using the paradigms described occurred in endothelial cells lining the vasculature of the brain, adding support to previous observations that these cells constitute important targets for circulating pyrogens (36).…”
Section: Discussionsupporting
confidence: 89%
“…Recent evidence, however, suggests that COX-2 induction, at least in peripheral tissue, such as the myocardium, can indeed be activated through this pathway (63). In the brain, studies have now shown that systemically administered IL-6 can induce nuclear STAT3 translocation in structures implicated in the fever response (22,51), namely endothelial cells lining the vasculature within the blood-brain barrier (BBB) and the sensory circumventricular organs (sCVOs), which lack an intact BBB. The same studies, however, did not address the precise functional consequence of IL-6-mediated genomic activation of these structures, including whether this humoral mediator can trigger PG synthesis.…”
mentioning
confidence: 99%
“…The OVLT belongs to the sensory circumventricular organs (CVOs), which all lack a tight blood-brain barrier but rather present a fenestrated endothelium. Endogenous pyrogens activate nuclear factor-kappa B (NF-kB) (Laflamme and Rivest, 1999) and signal transducer and activator of transcription-3 (STAT3) (Rummel et al, 2005), transcription factors in brain endothelial cells of a particular locus of the POA called the median preoptic nucleus (MnPO). These transcription factors target several genes among which those encoding the cyclooxygenase 2 (COX2) and the microsomal PGE synthase 1 (mPGES1), both involved in the synthesis of prostaglandin (PG) E 2 (PGE 2 ) (Nadjar et al, 2005;Rummel et al, 2005Rummel et al, , 2006.…”
Section: The Humoral Pathwaymentioning
confidence: 99%
“…The expression of these target gene proteins is increased through proinflammatory transcription factors, including the signal transducer and activator of transcription 3 (STAT3) and nuclear factor-jB (NFjB). Recently, we and others have used immunohistochemical detection of STAT3 or NFjB to determine IL6 (STAT3)-or LPS/IL1b-induced (NFjB) genomic activation of specific cell types and brain structures during inflammation and have revealed several hypothalamic nuclei that are implicated in the induction of ''sickness'' responses such as fever (Gautron et al, 2002;Harré et al, 2002Harré et al, , 2003Nadjar et al, 2003;Rummel et al, 2004Rummel et al, , 2005Rummel et al, , 2006Rummel et al, , 2008.…”
mentioning
confidence: 99%